L’immagine, la copia e il simulacro: Deleuze e Platone - Colombo, Andrea (Scenari, 2024)
This essay explores the evolution of Gilles Deleuze’s thought by comparing his works “Difference and Repetition” and “What is Philosophy?”. Initially, Deleuze advocates for a philosophy grounded in difference and repetition, moving away from Platonic transcendence towards a more immanent and differentiated view of thought. However, over three decades, a significant shift in his philosophical approach is observed. In “What is Philosophy?”, co-authored with Félix Guattari, the concept of “image” takes on a dual identity as both plane and construction, indicating a reevaluation of philosophy that cannot completely shed its pre-philosophical images. This paper argues that Deleuze, extending his investigation into immanence, no longer seeks a mere reversal of Platonism but a continual re-creation of thought that transcends traditional dichotomies, urging every philosopher to perpetually redefine the foundational concepts of philosophy.